Accumulation of stem sugar and its remobilisation in response to drought stress in a sweet sorghum genotype and its near‐isogenic lines carrying different stay‐green loci. (19th January 2017) - Ghate, T.; Deshpande, S.; Bhargava, S.
Abstract: Near isogenic lines (NILs) of sweet sorghum genotype S35 into which individual stay green loci were introgressed, were used to understand the contribution of Stay green loci to stem sugar accumulation and its remobilization under drought stress exposure. Sugar and starch content, activities of sugar metabolism enzymes and levels of their expression were studied in the 3rd (source) leaf from panicle and the 5th (sugar storing) internode of the three lines, in irrigated plants and in plants exposed to a brief drought exposure at the panicle emergence stage. Annotation of genes in the respective Stay green loci introgressed in the NILs was carried out using bioinformatics tools. The leaves of NILs accumulated more photoassimilates and the internodes accumulated more sugar, as compared to the parent S35 line. Drought stress exposure led to a decrease in the starch and sugar levels in leaves of all three lines, while an increase in sugar levels was observed in internodes of the NILs. Sugar fluxes were accompanied by alterations in the activities of sugar metabolizing enzymes as well as the expression of genes related to sugar metabolism and transport. Remobilization of sugars from the stem internodes was apparent in the NILs when subjected to drought stress, since the peduncle, which supports the panicle, showed an increase in the sugar content, even when photoassimation in source leaves was reduced. Several genes related to carbohydrate metabolism were located in the Stay green loci, which probably contributed to variation in the parameters studied.